Patterns of Eastern European urbanisation in the mirror of Western trends – Convergent, unique or hybrid?. (September 2019) - Taubenböck, H; Gerten, C; Rusche, K; Siedentop, S; Wurm, M
This paper presents a cross-sectional analysis of the urban land use patterns of 230 city regions in 34 European countries and an in-depth longitudinal analysis of 10 selected regions. The guiding question is whether the post-socialist transformation of urban spatial structure in Eastern European regions can be interpreted as an adaption process to Western-style urbanisation and how far a process of 'mimicry' has reached. Our empirical approach is based on a model designed to measure binary urban land use patterns with respect to spatial dispersion. As cities and city regions vary in spatial pattern and size, we calculate the dispersion index for three different standardised extents: squares of 25 and 50 km around the defined urban centres as well as city-adjusted accessibility isochrones. Our input layers are binary settlement classifications derived from multi-temporal Earth observation data. For the cross-sectional analysis, we cover entire Europe, and for the longitudinal analysis, we cover a sample of 10 cities for Western and Eastern Europe of predominantly capital cities of different sizes at four time steps – 1975, 1990, 2000 and 2010. We found significant differences between Western and Eastern European city regions as they have entered different stages of urbanisation. Eastern city regions are less populated, less urbanised, more dispersed and denser than regions in the West. Processes of post-socialist urban restructuring have definitely resulted in a change in land use patterns similar to that of Western Europe since the late 1950s. We nevertheless do not think that a 'catch-up' growth, leading to full convergence with Western-style urbanisation, will be a realistic future scenario. Eastern European urbanisation can best be characterised as hybrid: cities and city regions simultaneously manifest characteristics of convergent adaptation and path-dependency; they prove typical features of capitalist urbanisation, but relics of the socialist past are still omnipresent.